Pyoderma gangrenosum and Sweet syndrome – case report and literature review - Lis-Święty, Anna; Brzezińska-Wcisło, Ligia; Bergler-Czop, Beata; Wcisło-Dziadecka, Dominika (Dermatology Review/Przegląd Dermatologiczny, 2012)
Introduction. Sweet syndrome and pyoderma gangrenosum are two diseases from the neutrophilic dermatoses group in which inflammatory infiltrations consisting of mature granulocytes are present. Neutrophilic infiltrations in other extracutaneous localizations and different systemic disorders, i.e. autoimmunological connective tissue diseases, inflammatory bowel disease, tumours of internal organs and hematopoietic system, especially acute and chronic myeloid leukaemia, myelodysplastic syndrome and plasmacytoma, may co-exist in both diseases. It is possible for Sweet syndrome and pyoderma gangrenosum lesions to overlap, to co-exist and to occur sequentially in the same patient. Objective . Presentation of a patient with neutrophilic dermatosis presenting as a gangrenous ulcer with co-existing neutrophilia and fever. Case report. A 60-year-old woman was admitted to the Dermatology Department due to rapidly progressing ulceration of the right leg. In the periphery vesicular and pustular lesions were observed. Out-patient therapy with antibiotics was ineffective. Laboratory investigations revealed elevated erythrocyte sedimentation rate, C-reactive protein, hyperleukocytosis and neutrophilia. Histopathological examination was consistent with neutrophilic dermatosis. Therapy with systemic corticosteroids and cyclosporine A was introduced and fast improvement, i.e. diminishing level of inflammation indicators, and gradual progress in healing of the ulcer were observed. Conclusions . Existence of transitional forms may cause problems in diagnosis and classification of Sweet syndrome and pyoderma gangrenosum. Further observation of the patient in respect of development of systemic diseases is required.